Analysis of T-Spherical Fuzzy Matrix and Their Application in Multiattribute Decision-Making Problems. (27th September 2022) - Garg, Harish; Saad, Muhammad; Rafiq, Ayesha
Abstract : The aim of this study is to introduce an innovative concept of T-spherical fuzzy matrix, which is a hybrid structure of fuzzy matrix and T-spherical fuzzy set. This article introduces the square T-spherical fuzzy matrix and constant T-spherical fuzzy matrix and discusses related properties. Determinant and the adjoint of a square T-spherical fuzzy matrix are also established, and some related properties are investigated. An application of the T-spherical fuzzy matrix in decision-making problem with an illustrative example is discussed here. Then, in the end, to check capability and viability, a practical demonstration of the planned approach has also been explained.